2019
DOI: 10.21053/ceo.2017.01704
|View full text |Cite
|
Sign up to set email alerts
|

Is Hyperbaric Oxygen Therapy Effective in Cisplatin-Induced Ototoxicity in Rats?

Abstract: HBO was found effective for prevention of cisplatin-induced ototoxicity in rats. Our study differs from other studies regarding using a promising treatment, which does not expose subjects to extra stress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…They evaluated the cochlear function and morphological structures and reported that hearing functions and external shaky hair cell morphology were significantly preserved in the HBOT group. In another study, Cobanoglu et al [5] evaluated the antioxidant effect of HBOT in 30 adult Wistar rats in a cisplatin-induced ototoxicity model. They administered HBOT on the same day or 72 h after 15 mg/kg of cisplatin administration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They evaluated the cochlear function and morphological structures and reported that hearing functions and external shaky hair cell morphology were significantly preserved in the HBOT group. In another study, Cobanoglu et al [5] evaluated the antioxidant effect of HBOT in 30 adult Wistar rats in a cisplatin-induced ototoxicity model. They administered HBOT on the same day or 72 h after 15 mg/kg of cisplatin administration.…”
Section: Discussionmentioning
confidence: 99%
“…The DPOAE amplitudes above 3 dB of noise threshold were considered significant. [5] The signal-to-noise ratio (SNR) defined as the geometric average of 2f1-f2 cubic distortion products were used for the interpretation of the DPOAE results. The mean ratio of each subject was calculated.…”
Section: Dpoae Testmentioning
confidence: 99%
“…HBO has the ability to enhance antioxidant enzyme activity, reduce or eliminate edema in nerve tissue, accelerate the scavenging of free radicals, increase the content of blood oxygen, generate more ATP, promote capillary regeneration, and improve microcirculation. 33 Meanwhile, HBO therapy specifically inhibits apoptosis after injury by improving the metabolism of nerve cells and increasing the energy necessary for protein synthesis. 34 It is very likely that mitophagy occurs in cells through mitochondrial energy changes.…”
Section: Discussionmentioning
confidence: 99%
“…This issue of ROS damage from HBO is also a consideration for cisplatinum toxicity, since increased ROS are thought to be an important factor in cisplatinum-induced damage. Cobanoglu et al (2019) recently reported that HBO treatment of rats after receiving cisplatinum led to improved recovery after the insult compared to the untreated control group. Interestingly, in a study of cisplatinum-induced nephrotoxicity, Aydinoz et al (2007) showed that once-daily HBO provided benefit, while twice-daily HBO seemed to potentiate the damage.…”
Section: Oxygen As a Cochlear Therapeuticmentioning
confidence: 99%